Altered structure and functional connectivity of the central autonomic network in idiopathic rapid eye movement sleep behaviour disorder. (30th June 2020) - Li, Guanglu; Chen, Zhichun; Zhou, Liche; Zhao, Aonan; Niu, Mengyue; Li, Yuanyuan; Luo, Ningdi; Kang, Wenyan; Liu, Jun
Abstract: Evidence suggests peripheral autonomic structures may contribute to autonomic dysfunction in idiopathic rapid eye movement sleep behaviour disorder (iRBD). However, whether the central autonomic network (CAN) is affected in iRBD remains unclear. Magnetic resonance imaging data were acquired from 65 participants (32 patients with iRBD and 33 matched healthy controls). We investigated the CAN in patients with iRBD using a combined voxel‐based morphometry and resting‐state functional connectivity analysis and characterised the relationships between alterations of the CAN and autonomic symptoms. Patients with iRBD had significantly reduced grey matter volume in the brainstem, anterior cingulate and insula compared with healthy controls. Functional connectivity analysis revealed reduced functional connectivity between the brainstem and the cerebellum posterior lobe, temporal lobe and anterior cingulate in patients with iRBD. In patients with iRBD, both reduced grey matter volume and decreased functional connectivity of the CAN were negatively correlated with the Scales for Outcomes in Parkinson's Disease–Autonomic scores. The present study demonstrated that both the structure and the functional connectivity of the CAN were abnormal in patients with iRBD. In addition, correlation analysis suggested that CAN abnormalities may also play a role in the development of autonomic symptoms in iRBD.